Analisis Dampak Program Pertukaran Mahasiswa Merdeka Terhadap Hasil Belajar Mahasiswa Jurusan Matematika Universitas Negeri Manado - Yepta Juan Fiali Launde; John Robby Wenas; Nita Anggriani (Journal on Education, 2024)
Mathematics is an important basic science, because logical thinking, analytical and problem-solving skills are needed in various fields such as business, technology, health and the environment. Strong mathematics students are expected to be able to adapt, innovate, and contribute to solving global problems, so that their learning outcomes are important in preparing them to face global challenges in the future. In the current era, the government product curriculum is known as the Merdeka Curriculum, or Independent Learning Independent Campus (MBKM), one of the programs of which consists of the PMM program. The aim of this research is to analyze the positive impact of the PMM program which is so important on mathematics learning outcomes which can provide insight into how well this program prepares students to face global challenges in the future. The research method used is a qualitative research method with a case study research design. The results obtained from this research are that the impact of the PMM program on the learning outcomes of students majoring in mathematics at Unima is categorized into the good category with an overall percentage score of 85.7%.